Memahami Pertumbuhan dan Perkembangan Peserta Didik: Kunci Sukses Proses Pembelajaran - Insani Herlando, Husnul; Deliani, Nurfarida; Batubara, Juliana (Cahaya Ilmu Bangsa Institute, 2024)
This study aims to identify the effect of teacher understanding of learners' growth and development on the quality of learning quality at MAN 1 Padang Pariaman. In the context of education, teachers' understanding of students' developmental stages can influence the way they design and implement implement learning, thus impacting on students' motivation and learning outcomes. students' motivation and learning outcomes. This research uses a descriptive qualitative approach with two main data collection techniques: semi-structured interviews and classroom observations.Participants consisted of five teachers and students. Interviews were conducted to explore teachers' understanding of student development as well as the application of teaching strategies that are tailored to the developmental stage of students. Meanwhile, classroom observations were conducted to directly observe the implementation of these strategies in learning activities. The collected data were analyzed using thematic analysis to identify the main themes that emerged from the interviews and observations. The results show that teachers who understand student development tend to create a more inclusive, supportive and effective learning atmosphere. Conversely, a lack of understanding of students' developmental stages can lead to low student motivation and learning outcomes. This research provides insight into the importance of teachers' understanding of student development in improving the quality of learning that is more in line with students' needs.